2010
DOI: 10.1590/s0100-204x2010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Leaf plasticity in successive selection cycles of 'Saracura' maize in response to periodic soil flooding

Abstract: -The objective of this work was to assess the effect of successive selection cycles on leaf plasticity of 'Saracura' maize BRS-4154 under periodical flooding in field conditions. Soil flooding started at the six-leaf stage with the application of a 20-cm depth water layer three times a week. At flowering, samples of leaves were collected and fixed. Paradermic and transverse sections were observed under photonic microscope. Several changes were observed throughout the selection cycles, such as modifications in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 28 publications
3
30
0
8
Order By: Relevance
“…Catoni et al (2012) reported lower palisade parenchyma thickness under lower temperatures and higher water availability in Cistus species. Palisade parenchyma is also directly related to photosynthesis (Souza et al, 2010) and shade leaves show a decrease of palisade parenchyma thickness in many plant species (Eschrich et al, 1989;Terashima et al, 2006). Therefore, as observed on the …”
Section: Resultsmentioning
confidence: 83%
“…Catoni et al (2012) reported lower palisade parenchyma thickness under lower temperatures and higher water availability in Cistus species. Palisade parenchyma is also directly related to photosynthesis (Souza et al, 2010) and shade leaves show a decrease of palisade parenchyma thickness in many plant species (Eschrich et al, 1989;Terashima et al, 2006). Therefore, as observed on the …”
Section: Resultsmentioning
confidence: 83%
“…Field established plants had thicker epidermical faces, probably due to their exposure to the weather conditions, especially the higher light intensity. This feature can be useful for reflecting excessive radiation and reducing water loss (SOUZA et al, 2010). Leaf lamina thickness was also higher in field grown plants (Table 2).…”
Section: Leaf Anatomymentioning
confidence: 97%
“…One of them is the presence of a group of cells called motor bulliform cells, which are present in the upper side of the leaves, arranged in longitudinal rows parallel to the ribs, and may be grouped in a cross section of 2 to 8 cells (Alvarez et al, 2008). These cells promote curling of leaves under conditions of excessive loss of water or even flooding, reducing its specific area and forming a spiral (Souza et al, 2010). It was observed that most plants under a drought treatment had this leaf rolling condition after two days of irrigation, especially during the hottest times of the day.…”
Section: Fig 11mentioning
confidence: 99%